1988
DOI: 10.1128/jb.170.3.1220-1226.1988
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of an electrophoretically labile hydrogenase activity of Escherichia coli K-12

Abstract: A mutant of Escherichia coli K-12 is described that is specifically impaired in only one hydrogenase isoenzyme. By means of Tn5-mediated insertional mutagenesis, a class of mutants was isolated (class I) that had retained 20% of the overall hydrogenase activity. As determined by neutral polyacrylamide gel electrophoresis, the mutant contained normal amounts of the hydrogenase isoenzymes 1 and 2. Therefore, the hydrogenase activity affected seemed to be electrophoretically labile and was called hydrogenase L. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
21
0

Year Published

1989
1989
1994
1994

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Boxer and co-workers (4, 28) purified HYD1 and an active fragment of HYD2 and reported that these two isoenzymes are immunologically distinct. Other descriptions of hydrogenase purification from E. coli, to different levels of purity, can be found in the literature (1,5,13,14,31). Hydrogenases that had been purified to homogeneity had apparent molecular weights of 56,000 (1), 58,000 (14), and 200,000 (28).…”
Section: Resultsmentioning
confidence: 99%
“…Boxer and co-workers (4, 28) purified HYD1 and an active fragment of HYD2 and reported that these two isoenzymes are immunologically distinct. Other descriptions of hydrogenase purification from E. coli, to different levels of purity, can be found in the literature (1,5,13,14,31). Hydrogenases that had been purified to homogeneity had apparent molecular weights of 56,000 (1), 58,000 (14), and 200,000 (28).…”
Section: Resultsmentioning
confidence: 99%
“…Although several reports suggest a respiratory role for hydrogenase 2, our previous results (28) suggested that a labile hydrogenase species was involved in H, uptake. In this study, further evidence is provided in favor of the latter model.…”
mentioning
confidence: 93%
“…The underlying genetic regulation mechanisms, however, are still poorly understood. Although more than 10 genetic loci have been described thus far, mapping near 58 min (11,15,22,24,30), 65 min (15,28), and 77 min (31), none of these searches was exhaustive, and it is still unknown whether these studies revealed all loci involved in H, metabolism. We therefore undertook a systematic screening of a large number of Tn5 insertion mutants; this search yielded one new locus, which was further characterized.…”
mentioning
confidence: 99%
See 2 more Smart Citations